2017
DOI: 10.21873/cgp.20024
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Matrix Metalloproteinase-1 Genotypes to Hepatocellular Carcinoma Susceptibility in Taiwan

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The results showed that overexpression of FOXP3 in HepG2 cells upregulated the expression of MMP-1. Furthermore, the migration and invasion ability of HCC cells were observed to increase after knocking down FOXP3, supported by the findings that overexpressed MMP-1 was associated with an elevated metastasis capacity, invasion and migration ability of the HCC cells ( 35 , 36 ). Base on the result, we concluded that FOXP3 in HCC cells promotes the metastasis of HCC through the regulation of the expression of MMP-1.…”
Section: Discussionsupporting
confidence: 55%
“…The results showed that overexpression of FOXP3 in HepG2 cells upregulated the expression of MMP-1. Furthermore, the migration and invasion ability of HCC cells were observed to increase after knocking down FOXP3, supported by the findings that overexpressed MMP-1 was associated with an elevated metastasis capacity, invasion and migration ability of the HCC cells ( 35 , 36 ). Base on the result, we concluded that FOXP3 in HCC cells promotes the metastasis of HCC through the regulation of the expression of MMP-1.…”
Section: Discussionsupporting
confidence: 55%
“…MMP-1 is also named collagenase-1, due to the fact that it promotes degradation of the interstitial collagens and is normally regulated by TIMP-1. Overexpression of both MMP-1 and TIMP-1 is associated with an elevated invasive and migratory capacity of the HCC cells, most likely by ECM degradation in the process of EMT [42]. Overexpression of miR-526b is associated with increased cell proliferation, venous infiltration, and a poor prognosis, and MMP-1 is recognized as a direct target of miR-526b [43].…”
Section: Mmps With a Demonstrated Role In The Emt Of Invasive Hccmentioning
confidence: 99%
“…MMP-2 together with MMP-9, are the two most common progression markers correlated with invasion and metastasis in various tumor, especially HCC 15 , 16 . Although MMP1 has been more commonly reported to be expressed in non-neoplastic liver tissues 17 , it has also been shown to be associated with invasion and migration in HCC by extracellular matrix (ECM) degradation in the epithelial-mesenchymal transition (EMT) 18 . MMP1 can be expressed with a low positive rate under normal conditions in a wide range of cells including stromal fibroblasts, macrophages, endothelial cells and epithelial cells.…”
Section: Introductionmentioning
confidence: 99%